A poly (glycerol-sebacate-acrylate) nanosphere enhanced injectable hydrogel for wound treatment - Luo, Jiajia; Sun, Fenglei; Rao, Pinhua; Zhu, Tonghe; Liu, Yonghang; Du, Juan; Chen, Sihao; Jin, Xiangyun; Jin, Jiale; Chai, Yi (Frontiers in Bioengineering and Biotechnology, 2023)
Wound repair remains a huge clinical challenge, which can cause bleeding, infection, and patient death. In our current research, a bioactive, injectable, multifunctional composite hydrogel doped with nanospheres was prepared with antibacterial and angiogenesis-promoting functions for the treatment of wounds. Amino groups in ε-polylysine (ε-EPL) undergo dynamic Schiff base reaction cross-linking with oxidized hyaluronic acid (OHA), and F127 exhibits unique temperature sensitivity to form an injectable thermosensitive hydrogel (FHE10), which can form a hydrogel to cover the wound at body temperature. Nanospheres (PNs) prepared using poly(glyceryl-sebacate-acrylate) (PGSA) were loaded into hydrogels (FHE10) for promoting wound repair. The prepared FHE10 exhibited rapid gelation, good injectable abilities, and showed resistance to the flourish of Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). In vitro investigations showed that FHE10 had good hemocompatibility and cytocompatibility. FHE10@PNs exhibited good proliferation, migration, and tube formation of human umbilical vein endothelial cells (HUVECs) and human foreskin fibroblasts (HFF-1). Furthermore, FHE10@PNs significantly promoted reepithelialization and collagen deposition as well as micro-vascularization compared with the use of FHE10 or PNs alone, thereby accelerating the repair of wounds. In general, this study demonstrated that the multifunctional injectable composite hydrogel showed great potential in wound treatment.